2001
DOI: 10.1002/hed.1046
|View full text |Cite
|
Sign up to set email alerts
|

Pain as sign of recurrent disease in head and neck squamous cell carcinoma

Abstract: This study confirms that each pain complaint after intentional curative treatment should be regarded as a warning sign. Recurrence of disease without preceding pain complaints (30%) emphasizes the importance of a thorough follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 11 publications
3
30
0
1
Order By: Relevance
“…They reported high level of problems in all the domains and rated their overall physical condition and overall quality of life as being poor, supporting the observation of previous study. 28 As stated by Smit et al 29 most patients with proven recurrent disease report pain complaints as the first symptom which was also observed in the present study. The authors also concluded that each pain complaint after intentional curative treatment should be regarded as a warning sign 29 and may reflect survival rate 30 but however, we can draw any certain conclusions from our study duty to limited sample size in this group of patients.…”
Section: Jaisani and Biliga Health Renaissance 2013; Vol 11 (No2);125-supporting
confidence: 88%
“…They reported high level of problems in all the domains and rated their overall physical condition and overall quality of life as being poor, supporting the observation of previous study. 28 As stated by Smit et al 29 most patients with proven recurrent disease report pain complaints as the first symptom which was also observed in the present study. The authors also concluded that each pain complaint after intentional curative treatment should be regarded as a warning sign 29 and may reflect survival rate 30 but however, we can draw any certain conclusions from our study duty to limited sample size in this group of patients.…”
Section: Jaisani and Biliga Health Renaissance 2013; Vol 11 (No2);125-supporting
confidence: 88%
“…An increasing number of studies focus on the quality of life (QOL) of SCCHN patients [3,15,17,18,19,24,25,26,27,28,29,30,31,32,33,34,35,38,39,40,41,42]. QOL is multifactorial and subjective, and improvement in cancer-related symptoms can be achieved through primary assessment and intervention for problems as they arise [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35].…”
Section: Methodsmentioning
confidence: 99%
“…QOL is multifactorial and subjective, and improvement in cancer-related symptoms can be achieved through primary assessment and intervention for problems as they arise [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. For example, the initial measurement of pain after treatment is more likely to predict pain status contributing to a decrease in the overall QOL after primary-stage SCCHN [3,15,17,18,19,24,25,26,27,28,29,30,31,32,33,34,35,38,39,40,41,42]. While such issues are clearly relevant, no studies have used qualitative methods to elucidate factors associated with the under-reporting of suffering in individuals in this patient population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perineural spread of tumor was not observed in any patient on the MRI study. cause such referred pain [1][2][3][4][5][6]10]. The location of the disorder may thus be far more important than its etiology for this symptom.…”
Section: Resultsmentioning
confidence: 99%